556 A Matched-Pair Analysis of Patients with Ischemic Strokes Undergoing Thrombectomy Using the BOBBY Balloon Guide Catheter. (April 2023) - Kim, Lily H.; Choi, John H.; Wolman, Dylan; Pendharkar, Arjun Vivek; Dodd, Robert L.; Do, Huy M.; Heit, Jeremy; Telischak, Nicholas
Abstract : INTRODUCTION: Endovascular thrombectomy has become the standard-of-care in treatment of large-vessel occlusion. Despite evidence of enhanced clot retrieval with balloon guide catheters (BGC), their routine use is yet to be widely adopted possibly due to incompatibility of past generation BGCs with large bore intermediate catheters. The next-generation BOBBY BGC is compatible with the 0.070-inch SOFIATM Flow Plus catheter. METHODS: We conducted a retrospective study of 112 thrombectomy cases utilizing BGC (N = 56) and non-BGC (N=56) methods. Sixty consecutive thrombectomy cases that used BOBBYTM BGC (MicroVention, Aliso Viejo, CA) at a single institution between 2/2021-3/2022 were identified. Of them, 56 BGC cases were 1:1 matched with non-BGC cases performed between 4/2016-12/2021 by proceduralists, age (±10 years), gender, stent retriever + aspiration device versus aspiration-only, and site of occlusion. First-pass effect was defined as Thrombolysis In Cerebral Infarction scale ≥IIB with a single pass, and good functional outcome as Modified Rankin Scale ≤2. RESULTS: BGC and non-BGC cohorts had similar mean age (67 versus 69 years), gender distribution (44.6%, 48.2% females), mean initial National Institutes of Health Stroke Scale (14.5, 14), and median pre-treatment ischemic core volumes (12.5 ml, 11 ml). BGC and non-BGC cases had similar rates of single pass (58.9%, 55.4%), first-pass effect (57.1%, 50.0%), and complications (5.4%, 8.9%). In aspiration-only cases, adding BGC led to a significantly higher rate of first-pass effect (71.4% vs 50.0%, P = 0.01). BGC was associated with higher likelihood of achieving good functional outcome at discharge (OR 2.30, P = 0.01). No additional procedural time was required for BGC cases (46.7 versus 48.4 minutes). CONCLUSIONS: An initial one-year experience from a tertiary academic center shows BGC can be safely adopted with comparable procedural efficacy, benefits to aspiration-only techniques, and earlier functional improvement when compared to conventional guide catheter cases.